2009
DOI: 10.1021/tx900360w
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Exposure to Zinc Chromate Induces Centrosome Amplification and Spindle Assembly Checkpoint Bypass in Human Lung Fibroblasts

Abstract: Hexavalent chromium (Cr(VI)) compounds are known human lung carcinogens. Solubility plays an important role in its carcinogenicity with the particulate or insoluble form being the most potent. Of the particulate Cr(VI) compounds, zinc chromate appears to be the most potent carcinogen, however, very few studies have investigated its carcinogenic mechanism. In this study, we investigated the ability of chronic exposure to zinc chromate to induce numerical chromosome instability. We found no increase in aneuploid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 49 publications
8
34
0
Order By: Relevance
“…They suggested that one possible mechanism for lead chromate-induced carcinogenesis is through centrosome dysfunction, leading to the induction of aneuploidy. The same group (Holmes et al, 2010) also showed that chronic exposure to zinc chromate, another particulate Cr(VI) compound, induces centrosome amplification and spindle checkpoint bypass using human lung fibroblasts. Arsenic is another environmental toxicant, and the biological effects of arsenic have been studied.…”
Section: Centrosome Abnormalities In Human Lung Cancer: Mechanisms Camentioning
confidence: 93%
“…They suggested that one possible mechanism for lead chromate-induced carcinogenesis is through centrosome dysfunction, leading to the induction of aneuploidy. The same group (Holmes et al, 2010) also showed that chronic exposure to zinc chromate, another particulate Cr(VI) compound, induces centrosome amplification and spindle checkpoint bypass using human lung fibroblasts. Arsenic is another environmental toxicant, and the biological effects of arsenic have been studied.…”
Section: Centrosome Abnormalities In Human Lung Cancer: Mechanisms Camentioning
confidence: 93%
“…Disruption of the SAC by Cr(VI) particles was manifested by the formation of chromosome spreads showing centromere spreading, premature centromere division, and premature anaphase [34,35]. In addition, levels of Mad2 expression were decreased indicating that the SAC was satisfied and the cells were allowed to proceed to anaphase [35].…”
Section: Carcinogenic Metalsmentioning
confidence: 99%
“…Centrosome amplification is a third potential mechanism for Cr(VI)-induced aneuploidy [33,34,39]. Zinc chromate, in particular, was shown to induce a prolonged G2 arrest along with an increase in centriolar defects [34]; this suggests multiple mechanisms for chromium-induced centrosome amplification such as multiple rounds of centrosome duplication during the prolonged G2 arrest, centriole splitting and acentriolar centrosome formation.…”
Section: Carcinogenic Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of zinc chromate carcinogenesis are still poorly understood. Recently, an article was published [Holmes et al, 2010] investigating the ability of chronic exposure to zinc chromate to induce numerical chromosome instability in human lung fibroblasts in vitro. It was found that exposures longer than 24 h induced concentration-and timedependent increases in hypoploid, hyperploid and polyploid cells.…”
Section: Other Potential Aneugenic Exposures In Occupational Settingsmentioning
confidence: 99%